Predictors and outcomes of sustained, intermittent or never achieving remission in patients with recent onset inflammatory polyarthritis: results from the Norfolk Arthritis Register. (24th May 2016) - Cook, Michael J.; Diffin, Janet; Scirè, Carlo A.; Lunt, Mark; MacGregor, Alex J.; Symmons, Deborah P. M.; Verstappen, Suzanne M. M.
Abstract: Objectives. Early remission is the current treatment strategy for patients with inflammatory polyarthritis (IP) and RA. Our objective was to identify baseline factors associated with achieving remission: sustained (SR), intermittent (IR) or never (NR) over a 5-year period in patients with early IP. Methods. Clinical and demographic data of patients with IP recruited to the Norfolk Arthritis Register (NOAR) were obtained at baseline and years 1, 2, 3 and 5. Remission was defined as no tender or swollen joints (out of 51). Patients were classified as NR or PR, respectively, if they were in remission at: no assessment or ⩾3 consecutive assessments after baseline, and IR otherwise. Ordinal regression and a random effects model, respectively, were used to examine the association between baseline factors, remission group and HAQ scores over time. Results. A total of 868 patients (66% female) were included. Of these, 54%, 34% and 12% achieved NR, IR and SR, respectively. In multivariate analysis, female sex (odds ratio, OR 0.47, 95% CI: 0.35, 0.63), higher tender joint count (OR = 0.94, 95% CI: 0.93, 0.96), higher HAQ (OR = 0.59, 95% CI: 0.48, 0.74), being obese (OR = 0.70, 95% CI: 0.50, 0.99), hypertensive (OR = 0.67, 95% CI: 0.50, 0.90) or depressed (OR = 0.74, 95% CI: 0.55, 1.00) at baseline were independent predictors of being in a lower remission group. IR and SR were associated with lower HAQ scores over time and lower DAS28 at year 5. Conclusion. Women with higher tender joint count and disability at baseline, depression, obesity and hypertension were less likely to achieve remission. This information could help when stratifying patients for more aggressive therapy.